Web accessibility: Filtering redundant and irrelevant information improves website usability for blind users. Issue 111 (March 2018) - Giraud, Stéphanie; Thérouanne, Pierre; Steiner, Dirk D.
Highlights: Applying accessibility norms does not guarantee a good experience for blind users. Web design should take into account the specific needs of blind users. Filtering irrelevant and redundant information is a major need for blind users. Filtering information increases performance and satisfaction during web navigation. Filtering information substantially lowers cognitive load during web navigation. Abstract: Accessibility norms for the Web are based on the principle that everybody should have access to the same information. Applying these norms enables the oralization of all visual information by screen readers used by people with blindness. However, compliance with accessibility norms does not guarantee that users with blindness can reach their goals with a reasonable amount of time and effort. To improve website usability, it is necessary to take into account the specific needs of users. A previous study revealed that a major need for users with blindness is to quickly reach the information relevant to the task, by filtering redundant and irrelevant information. We conducted three experiments in which seventy-six participants with blindness performed tasks on websites which filtered or not irrelevant and redundant information. Cognitive load was assessed using the dual-task paradigm and the NASA-RTLX questionnaire. The results showed a substantial benefit for information filtering regarding participants' cognitive load, performance, and satisfaction. Thus, this study provides cogent arguments for improving usability of websites by information filtering for users with blindness.